Characterization of an Atmospheric-Pressure Argon Plasma Generated by 915 MHz Microwaves Using Optical Emission Spectroscopy - Miotk, Robert; Hrycak, Bartosz; Jasiński, Mariusz; Mizeraczyk, Jerzy (Journal of Spectroscopy, 2017)
The paper presents the investigations of an atmospheric-pressure argon plasma generated at 915 MHz microwaves using the optical emission spectroscopy (OES). The 915 MHz microwave plasma was inducted and sustained in a waveguide-supplied coaxial-line-based nozzleless microwave plasma source. The aim of presented investigations was to estimate parameters of the generated plasma, that is, excitation temperature of electrons Texc, temperature of plasma gas Tg, and concentration of electrons ne. Assuming that excited levels of argon atoms are in local thermodynamic equilibrium, Boltzmann method allowed in determining the Texc temperature in the range of 8100–11000 K. The temperature of plasma gas Tg was estimated by comparing the simulated spectra of the OH radical to the measured one in LIFBASE program. The obtained Tg temperature ranged in 1200–2800 K. Using a method based on Stark broadening of the Hβ line, the concentration of electrons ne was determined in the range from 1.4 × 1015 to 1.7 × 1015 cm−3, depending on the power absorbed by the microwave plasma.